Does aerobic exercise effect pain sensitisation in individuals with musculoskeletal pain? A systematic review - Tan, Lynn; Cicuttini, Flavia M; Fairley, Jessica; Romero, Lorena; Estee, Mahnuma; Hussain, Sultana Monira; Urquhart, Donna M (BMC musculoskeletal disorders, 2022)
Background Pain sensitisation plays a major role in musculoskeletal pain. However, effective treatments are limited, and although there is growing evidence that exercise may improve pain sensitisation, the amount and type of exercise remains unclear. This systematic review examines the evidence for an effect of aerobic exercise on pain sensitisation in musculoskeletal conditions. Methods Systematic searches of six electronic databases were conducted. Studies were included if they examined the relationship between aerobic physical activity and pain sensitisation in individuals with chronic musculoskeletal pain, but excluding specific patient subgroups such as fibromyalgia. Risk of bias was assessed using Cochrane methods and a qualitative analysis was conducted. Results Eleven studies (seven repeated measures studies and four clinical trials) of 590 participants were included. Eight studies had low to moderate risk of bias. All 11 studies found that aerobic exercise increased pressure pain thresholds or decreased pain ratings in those with musculoskeletal pain [median (minimum, maximum) improvement in pain sensitisation: 10.6% (2.2%, 24.1%)]. In these studies, the aerobic exercise involved walking or cycling, performed at a submaximal intensity but with incremental increases, for a 4-60 min duration. Improvement in pain sensitisation occurred after one session in the observational studies and after 2-12 weeks in the clinical trials. Conclusions These findings provide evidence that aerobic exercise reduces pain sensitisation in individuals with musculoskeletal pain. Further work is needed to determine whether this translates to improved patient outcomes, including reduced disability and greater quality of life.